2020
DOI: 10.3389/fmars.2020.00205
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of DNA Methylation in Transcriptomic Plasticity of Early Stage Sea Urchins: Developmental and Maternal Effects in a Kelp Forest Herbivore

Abstract: Gene expression plasticity can confer physiological plasticity in response to the environment. However, whether epigenetic marks contribute to the dynamics of gene expression is still not well described in most marine invertebrates. Here, we explored the extent and molecular basis of intra-and intergenerational plasticity in the purple sea urchin, Strongylocentrotus purpuratus, by examining relationships between changes in DNA methylation, transcription, and embryo spicule length. Adult urchins were conditione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 95 publications
5
42
0
Order By: Relevance
“…CpG methylation is more abundant in S. purpuratus relative to most invertebrates, likely because of its phylogenetic position as a basal deuterostome (Regev, Lamb, & Jablonka, 1998). TGP linked to maternal effects have been observed in S. purpuratus for traits including egg protein content, larval body size, gene expression, and DNA methylation Strader et al, 2020;Strader, Wong, Kozal, Leach, & Hofmann, 2019;Wong, Johnson, Kelly, & Hofmann, 2018;Wong, Kozal, Leach, Hoshijima, & Hofmann, 2019) alongside similar observations in congeneric Strongylocentrotus spp. (Ding et al, 2019) and other urchin genera (Clark et al, 2019;Karelitz, Lamare, Patel, Gemmell, & Uthicke, 2019;Wong & Hofmann, 2021).…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…CpG methylation is more abundant in S. purpuratus relative to most invertebrates, likely because of its phylogenetic position as a basal deuterostome (Regev, Lamb, & Jablonka, 1998). TGP linked to maternal effects have been observed in S. purpuratus for traits including egg protein content, larval body size, gene expression, and DNA methylation Strader et al, 2020;Strader, Wong, Kozal, Leach, & Hofmann, 2019;Wong, Johnson, Kelly, & Hofmann, 2018;Wong, Kozal, Leach, Hoshijima, & Hofmann, 2019) alongside similar observations in congeneric Strongylocentrotus spp. (Ding et al, 2019) and other urchin genera (Clark et al, 2019;Karelitz, Lamare, Patel, Gemmell, & Uthicke, 2019;Wong & Hofmann, 2021).…”
Section: Introductionmentioning
confidence: 66%
“…(Downey-Wall et al, 2020;Johnson, Sirovy, Casas, La Peyre, & Kelly, 2020), and arthropods (Bonasio et al, 2012;Gatzmann et al, 2018;Glastad, Gokhale, Liebig, & Goodisman, 2016;Kvist et al, 2018) with exceptions to this pattern evident in some species and cell types (de Mendoza et al, 2019;Flores et al, 2012;Wang, Song, et al, 2021). By contrast, inducible changes in invertebrate gene expression in response to environmental variation have frequently possessed insignificant relationships with differential GBM (Arsenault et al, 2018;Dixon et al, 2018;Downey-Wall et al, 2020;Strader et al, 2020). In some arthropods, molluscs, and nematodes, there is evidence that GBM aids in regulating alternative splicing and exon skipping (Flores et al, 2012;Gao et al, 2012;Li-Byarlay et al, 2013;Libbrecht, Oxley, Keller, & Kronauer, 2016;Song, Li, & Zhang, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several lines of evidence suggested that maternal exposure to different conditions affected the DNA methylation status of the offspring [ 83 , 84 ]. In particular, several genes involved in mechanisms of transcriptional regulation, including DNA modification and metabolism, as well in protein ubiquitination, were identified as differentially methylated in the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported maternal effects in gene expression including in a perennial herb (Videvall et al, 2016), coral (Dixon et al, 2015), pipefish (Beemelmanns & Roth, 2016) and stickleback (Metzger & Schulte, 2016;Mommer & Bell, 2014;Shama et al, 2016), and maternal environments have also been demonstrated to affect DNA methylation of sea urchin (Strader et al, 2020). Videvall et al (2016) showed that gene expression patterns were distinct between parental populations of 12-week-old seedling of the perennial herb Arabidopsis lyrata, and expression in intraspecific hybrids was frequently more similar to that of the maternal than paternal population.…”
Section: Maternal Effects In Coral Fitness Are Reflected In Gene Exmentioning
confidence: 98%